Khairat death fund as an instrument to cope the funeral cost in Muslim community in Malaysia - Nuur Halimatus Sa'adiah Masrukhin (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A)-- Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2017